Perancangan Interior Galeri Patung Lilin Tokoh Srimulat di Surabaya dengan Konsep "A Comedian Journey As Friend" - Hariyanto, Eric; nugroho, martino dwi; Nilasari, Poppy Firtatwentyna (Intra, 2014)
Srimulat is one artist that is very popular comedy group from Surabaya and people enjoy doing in the 1980s. Wax sculpture is a sculpture made of wax in the melt up to 74 degrees Celsius and a means of supporting the display. For it is necessary to have a tool that can provide a facility to introduce Srimulat with a wax sculpture gallery. In this thesis, the author discusses about the design of a wax sculpture gallery that presents an atmosphere Srimulat periodically and information - information about Srimulat. Taking the concept of "Journey As A Comedian Friend" which is a concept Srimulat journey from the beginning, and to the glorious era terakhinya Srimulat, starting from the creation of space in order to attract visitors by optimizing modern design combined with a pop art style. Srimulat wax figure sculpture gallery is expected to be one - the only place that provides a means of education and introduce Srimulat again to be remembered by the people of Surabaya and Indonesia.